A rare translocation in a patient with adult type polycystic renal disease - Yuece, Hueseyin; Oezbey, Uelkue; Ceylan, Guelay Guelec; Elvas, Halit (Ortadogu Ad Pres & Publ Co, 2007)
Adult type polycystic renal disease (APKD) is an autosomal dominant disease with cardinal symptoms like renal cysts, liver cysts and intracranial aneurysms. The aim of this study was to do pedigree analysis on the inheritance model of this disease and to emphasize the genetic Counselling process in APKD. The conventional cytogenetic analysis of the patient revealed a karyotype of 46,XX, t(3;5)(p,26: :q13), der(5)(pter -> q13). To our knowledge, this is the first case reported in the literature that was analyzed for APKD and determined to be t(3;5) cytogenetically. We suggest that the karyotype determined in the case with APKD may be a contributing factor for the ethiopathogenesis of the disease.
Keywords: polycystic kidney; autosomal dominant; chromosome aberrations; phenotype